The Modern Fundamentals of Golf - Hogan, Ben, 1912-1997 and Wind, Herbert Warren (London Hamlyn, 1957)
Contains the secrets of the swing that made Ben Hogan a great shotmaker. The book concentrates on the fundamentals of grip, stance, posture and the swing. It gives jargon-free advice complemented by detailed instructions.
Include Illustration
Keywords: Golf